Digital Literature - M. Badru Tamam; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
- The purpose of this library research is to describe (a). Principles of digital literary learning, (b). The concept of digital literary learning, (c). Assessment of digital literary learning. The method in this research uses a library study design. This research data is in the form of verbal exposure that contains information about digital literary learning, both regarding the underlying principles and alternative concepts of digital literary learning. This research data collection uses instruments in the form of recording or recording data. The data recording matrix is arranged based on needs and contains two elements, namely the description of the data source and the quoted data or data citation. The results of this study show that the Principles of digital literary learning include (a) Tradition, (b) Textuality, and (c) Methodological. The concept of digital literary learning refers to the theory of constructivism learning. That learners build knowledge and meaning from their experiences. Because learners have extensive backgrounds, experience, and skills, knowledge is built individually as learners work to understand the problems they face. Appropriate digital literary learning assessments use test assessments based on Bloom's taxonomy.